2021
DOI: 10.3389/fphar.2021.670479
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Models of Doxorubicin-Induced Cardiomyopathy in Rats and Mice. A Modern View From the Perspective of the Pathophysiologist and the Clinician

Abstract: Today the pharmacological possibilities of treating cancer are expanding and as a result, life expectancy is increasing against the background of chemotherapy and supportive treatment. In the conditions of successful antitumor treatment, complications associated with its toxic effect on healthy tissues and organs began to come to the fore. Anthracycline cardiomyopathy was the first serious cardiovascular complication to draw the attention of oncologists and cardiologists around the world. Anthracycline drugs s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 97 publications
5
57
0
Order By: Relevance
“…It has been shown that DOX-induced oxidative damage is associated with acute toxicity that induced by single dose of DOX in animals [ 40 , 41 ]. Furthermore, it has been reported that DOX toxicity can be divided into three categories: acute, subacute, and chronic toxicity [ 42 , 43 ]. Acute toxicity (short-term model) is induced following a single dose of DOX (dose usually ranges from approximately 5–30 mg/kg) and can lead to liver, renal, and cardiac damage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that DOX-induced oxidative damage is associated with acute toxicity that induced by single dose of DOX in animals [ 40 , 41 ]. Furthermore, it has been reported that DOX toxicity can be divided into three categories: acute, subacute, and chronic toxicity [ 42 , 43 ]. Acute toxicity (short-term model) is induced following a single dose of DOX (dose usually ranges from approximately 5–30 mg/kg) and can lead to liver, renal, and cardiac damage.…”
Section: Discussionmentioning
confidence: 99%
“…It is a highly successful chemotherapeutic medication for solid tumors, soft-tissue sarcoma, breast cancer, Hodgkin’s disease, Kaposi’s sarcoma, acute lymphoblastic leukemia, pediatric leukemia, lung cancer, lymphomas, and various metastatic malignancies [ 2 , 38 , 39 ]. The drug’s utility is limited owing to its large number of side effects, such as the suppression of the hematopoietic system, gastrointestinal disturbances, and baldness, with cardiac damage being the most dangerous [ 40 , 41 , 42 ].…”
Section: Mode Of Cardiotoxicity Inductionmentioning
confidence: 99%
“…The mechanisms of anthracycline cardiotoxicity are still being investigated in various experimental models [5]. All anthracyclines (doxorubicin, daunorubicin, epirubicin, idarubicin) have a general mode of ultrastructural myocardial damage, which is characterized by loss of myofibrils, expansion of the sarcoplasmic reticulum, cytoplasmic vacuolization, swelling of mitochondria and an increase in the number of lysosomes [9].…”
Section: Features Of the Development Of Doxorubicin Cardiomypathymentioning
confidence: 99%
“…Cardiotoxicity is dose-dependent and can develop during or immediately after the administration of doxorubicin, as well as some time after the end of treatment. Thus, acute and chronic doxorubicin cardiotoxicity is separated [4,5].…”
Section: Introductionmentioning
confidence: 99%